2001
DOI: 10.2118/72179-pa
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pore-Lining Chlorite on Petrophysical Properties of Low-Resistivity Sandstone Reservoirs

Abstract: Chlorite-bearing sandstones usually give low resistivity signals and are thus erroneously identified as nonpay zones, even if they exhibit good preserved porosities at depth. The purpose of this paper is to provide petrophysical and mineralogical laboratory measurements that help improve the log interpretation of these sandstones.The main results were obtained from a selection of reservoir cores. For sandstones having an amount of chlorite between 3 and 11 wt%, they show that the cementation index and saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The absolute permeability of the chlorite-rich sandstones commonly ranges between 0.01 and 30 mD, staying below 5 mD for most of the samples. Other potential reservoir problems caused by pore-lining chlorites include: (i) wireline log low-resistivity anomalies due to high saturation of irreducible water contained in chlorite aggregates, which may result in wrong evaluation of oil saturation (Moraes & De Ros 1992;Durand et al 2001); (ii) formation damage during well stimulation through acidification, owing to the precipitation of iron hydroxides, which makes the use of Fe-chelating agents necessary (Almon & Davies 1979;Baker et al 1993).…”
Section: Impact Of Chlorite In Santos Reservoirsmentioning
confidence: 99%
“…The absolute permeability of the chlorite-rich sandstones commonly ranges between 0.01 and 30 mD, staying below 5 mD for most of the samples. Other potential reservoir problems caused by pore-lining chlorites include: (i) wireline log low-resistivity anomalies due to high saturation of irreducible water contained in chlorite aggregates, which may result in wrong evaluation of oil saturation (Moraes & De Ros 1992;Durand et al 2001); (ii) formation damage during well stimulation through acidification, owing to the precipitation of iron hydroxides, which makes the use of Fe-chelating agents necessary (Almon & Davies 1979;Baker et al 1993).…”
Section: Impact Of Chlorite In Santos Reservoirsmentioning
confidence: 99%
“…Although the pore structure of RLP is poorer and the micropores are more developed in RLP reservoir than NP reservoir, the average porosity and permeability are better. Previous researches have shown that the clay mineral is an important factor to affect reservoir physical properties (Durand et al 2001;samakinde et al 2016;Yousef et al 2018). In general, the clay minerals filling in the pores will reduce the porosity and permeability and the pore structure becomes worse.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis of the correlation between the mass content of chlorite and the breakthrough pressure in clay minerals found that the mass content of chlorite was negatively correlated with the breakthrough pressure. As the chlorite content increased, the breakthrough pressure showed a decreasing trend (Durand et al, 2001;Wang et al, 2017). bound water.…”
Section: Low Resistance Causesmentioning
confidence: 99%